Evaluating Older Adults’ Engagement with Digital Interpretation Exhibits in Museums: A Universal Design-Based Approach - Lu Ai; Charanya Phaholthep (Heritage, 2025)
This paper develops and presents a system for museums to evaluate behavioural and experiential gains of older adult visitors when engaging with digital interpretation exhibits. The evaluation system is based on the Analytic Hierarchy Process (AHP), utilising existing evaluation methods for museum visitors and refining them into an approach suitable for investigating older visitors. Innovatively, it incorporates the universal design (UD) in museum digital exhibits, injecting strong momentum into creating inclusive museums. An in-depth evaluation was conducted on seven exhibitions across three newly constructed Chinese cultural tourism museums with different digital characteristics, presenting the results and findings through eighty-eight digital interpretation exhibits. Qualitative and quantitative data provide a nuanced picture of digital interpretation and interaction from the perspective of older visitors. The results demonstrate the factors influencing older adults’ engagement with digital interpretation exhibits in museums and how digital interpretation items attract or deter older visitors’ engagement in complex exhibition environments. This study utilised universal design principles to identify the limitations and barriers in digital interpretation for older visitors, analysed the correlation between UD and digital attraction power, explored the reasons behind these outcomes, and identified design recommendations for inclusive museum digital interpretation.